2013
DOI: 10.1161/circimaging.112.000170
|View full text |Cite
|
Sign up to set email alerts
|

Stress Hypoperfusion and Tissue Injury in Hypertrophic Cardiomyopathy

Abstract: Background— Ischemia and tissue injury are common in patients with hypertrophic cardiomyopathy. Cardiovascular magnetic resonance imaging offers combined evaluations of each phenomenon at sufficiently high resolution to examine transmural spatial distribution. In this prospective cohort study, we examine the spatial distribution of stress perfusion abnormalities and tissue injury in patients with hypertrophic cardiomyopathy. Methods and Results— One hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
(64 reference statements)
4
22
0
Order By: Relevance
“…On histology, Varnava et al found a poor interrelationship between myocardial fibrosis, small vessel disease and disarray [16]. These findings are also in accord with those of Tyan et al who semi-quantitatively assessed the distribution of perfusion abnormalities and tissue injury using CMR [42]. The absence of a dose–response relationship between reduced hyperemic MBF and the observed spatial distribution of LGE suggests that factors other than or beyond ischemia must be implicated in the pathogenesis of replacement fibrosis in HCM.…”
Section: Discussionsupporting
confidence: 69%
“…On histology, Varnava et al found a poor interrelationship between myocardial fibrosis, small vessel disease and disarray [16]. These findings are also in accord with those of Tyan et al who semi-quantitatively assessed the distribution of perfusion abnormalities and tissue injury using CMR [42]. The absence of a dose–response relationship between reduced hyperemic MBF and the observed spatial distribution of LGE suggests that factors other than or beyond ischemia must be implicated in the pathogenesis of replacement fibrosis in HCM.…”
Section: Discussionsupporting
confidence: 69%
“…Impairment of myocardial perfusion reserve has also been documented in some asymptomatic individuals with multiple cardiac risk factors in the Multi-Ethnic Study of Atherosclerosis, in asymptomatic patients with hypertrophic cardiomyopathy and in women with chest pain and systemic lupus erythematosus 10, 17 . A variety of CMRI techniques have been reported in single center studies of small groups of patients and these vary widely in terms of technical complexity, clinical applicability and system field strength (3.0T vs. 1.5T).…”
Section: Discussionmentioning
confidence: 96%
“…Though a great deal of our knowledge regarding microvascular ischemia in HCM should be credited to the use of SPECT and PET, MR imaging has now become an interesting alternative (21,81) because of its superior spatial resolution and its capability to help identify myocardial fibrosis (Table 3) (Fig 11) (Movie 5 [online]) (82)(83)(84). The perfusion MR sequences do not differ from those used in patients with coronary artery disease (eg, saturation-recovery fast gradientecho sequence).…”
Section: Role Of Mr Imaging In Assessing Microvascular Dysfunction Anmentioning
confidence: 99%
“…A decade later, it is fair to say that several gaps remain in our knowledge (94). We have learned that LGE is a common finding occurring in the majority of HCM patients (range, 33%-79%) with highly variable extent and intensity (83,95) and, consistent with prior pathologic studies, preferentially localized to the midwall of regions with maximum LV wall thickness (Table 1) (70,96,97). Stress-perfusion defects are often found in the same regions expressing LGE, although typically located in the subendocardial region rather than at midwall (Fig 11).…”
Section: Role Of Mr Imaging In Assessing Microvascular Dysfunction Anmentioning
confidence: 99%
See 1 more Smart Citation